Menentukan Prinsip dan Konsep Dasar Perancangan dan Pengembangan Kursi Roda - Fahrul Izza, Muhammad; Pasmawati, Yanti (UNIVERSITAS SERAMBI MEKKAH, 2024)
Wheelchairs are a vital aid for individuals with limited mobility, allowing them to remain active and independent. Although various models of wheelchairs are available on the market, challenges in ensuring comfort, safety and efficiency of use still exist. Therefore, designing and developing better wheelchairs is an urgent need to improve the quality of life and mobility of users. This research aims to determine important factors in designing optimal wheelchairs for the elderly and to disseminate the principles of wheelchair design. The final result of the brainstorming resulted in safe and comfortable wheelchair product specifications, including galvanized iron or chrome-plated black iron, foam and synthetic leather backrests, synthetic leather seats, as well as additional features such as airless tires, plastic-coated brakes, and foldable footrest